2013
DOI: 10.1021/bi400765d
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Temperature Dependence of Glycine—Betaine RNA Duplex Destabilization

Abstract: Glycine betaine stabilizes folded protein structure due to its unfavorable thermodynamic interactions with amide oxygen and aliphatic carbon surface area exposed during protein unfolding. However, glycine betaine can attenuate nucleic acid secondary structure stability, although its mechanism of destabilization is not currently understood. In this work we quantify glycine betaine interactions with the surface area exposed during thermal denaturation of nine RNA dodecamer duplexes with guanine-cytosine (GC) con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(25 citation statements)
references
References 38 publications
3
22
0
Order By: Relevance
“…It has been shown previously that cosolutes generally destabilize nucleic acid secondary structure via preferential interactions of the cosolute with the nucleobases in the unfolded state ( Lambert & Draper, 2007 ; Knowles et al, 2011 ), and differences in observed m-values are then due to differences in the chemistry of specific interactions of the cosolutes with given sequences. For example, betaine prefers G-C pairs, urea prefers A-T pairs, whereas polyethylene glycols have previously shown no distinct sequence preference ( Nordstrom et al, 2006 ; Spink, Garbett & Chaires, 2007 ; Knowles et al, 2011 ; Schwinefus et al, 2013 ). In determining these dependences, large global changes are often made; whereas for our RNA hairpin model system our sequence changes are small.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown previously that cosolutes generally destabilize nucleic acid secondary structure via preferential interactions of the cosolute with the nucleobases in the unfolded state ( Lambert & Draper, 2007 ; Knowles et al, 2011 ), and differences in observed m-values are then due to differences in the chemistry of specific interactions of the cosolutes with given sequences. For example, betaine prefers G-C pairs, urea prefers A-T pairs, whereas polyethylene glycols have previously shown no distinct sequence preference ( Nordstrom et al, 2006 ; Spink, Garbett & Chaires, 2007 ; Knowles et al, 2011 ; Schwinefus et al, 2013 ). In determining these dependences, large global changes are often made; whereas for our RNA hairpin model system our sequence changes are small.…”
Section: Resultsmentioning
confidence: 99%
“…Proline was a very strong destabilizer of RNA duplexes, in agreement with previous studies. ,,, The transition temperature at an RNA single strand unfolded fraction of 0.5 in 0 m proline decreased by approximately 5.5 °C to the same unfolded fraction in 1 m proline. Solutes, such as urea and glycine betaine, exhibited transition temperature attenuations of 2.6 °C and 2.7 °C, respectively, with a 12 base pair RNA duplex with similar GC content. Proline’s strong destabilization capability made proline a candidate as a chemical denaturant to fully unfold RNA duplexes, subject to proline’s solubility limit (next section).…”
Section: Resultsmentioning
confidence: 99%
“…High GC content duplexes were also destabilized to a greater extent in glycine betaine solutions when destabilization was monitored by thermal denaturation. ,, The greater destabilization of GC-rich relative to AT- or AU-rich nucleic acids was attributed to glycine betaine’s “isostabilizing” ability . Glycine betaine’s isostabilizing ability originated from the temperature dependence of glycine betaine interactions with nucleic acid surfaces . Since proline m -values obtained from thermal denaturation were obtained at temperatures well above room temperature, any temperature dependence of proline interactions with the unfolded RNA surface area would make comparison of m -values from thermal denaturation and predicted m -values in Figure tenuous at best.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tetramethylamonium chloride (TMAC) and glycine betaine have been reported to be isostabilizing agents, altering the melting temperature and making the hybridization solely dependent on oligonucleotide length, despite their GC content (Duby et al, 2004; Napolitano et al, 2004; Schwinefus et al, 2007). The destabilizing effect of such agents increases with increasing GC content, with almost no effect on poly(dAdT) (Schwinefus et al, 2013). On the other hand, some other components, such as urea, have the opposite effect, promoting a decrease in the strength of AT/U bonds more than GC base pairs (Schwinefus et al, 2007).…”
Section: Nucleic-acid Based Label-free Optical Biosensorsmentioning
confidence: 99%